2014
DOI: 10.1103/physrevlett.113.261605
|View full text |Cite
|
Sign up to set email alerts
|

AdS5×S5Mirror Model as a String Sigma Model

Abstract: Doing a double Wick rotation in the worldsheet theory of the light cone AdS5 × S 5 superstring results in an inequivalent, so-called mirror theory that plays a central role in the field of integrability in AdS/CFT. We show that this mirror theory can be interpreted as the light cone theory of a free string on a different background. This background is related to dS5 × H 5 by a double T duality, and has hidden supersymmetry. The geometry can also be extracted from an integrable deformation of the AdS5 × S 5 sig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
136
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(146 citation statements)
references
References 26 publications
9
136
1
Order By: Relevance
“…In particular, it was studied in [32] using the parameterization of [11], where it was found that the deformed metric in the limit κ → ∞ only corresponds to dS 5 × H 5 after applying some T -duality transformations. Furthermore, the same conclusion was reached more recently in [31] but with a different combination of T -dualities. What distinguishes the results of [32] and [31] is the way the various fields are scaled in the limit κ → ∞.…”
Section: Jhep10(2014)132 6 Conclusionsupporting
confidence: 57%
See 2 more Smart Citations
“…In particular, it was studied in [32] using the parameterization of [11], where it was found that the deformed metric in the limit κ → ∞ only corresponds to dS 5 × H 5 after applying some T -duality transformations. Furthermore, the same conclusion was reached more recently in [31] but with a different combination of T -dualities. What distinguishes the results of [32] and [31] is the way the various fields are scaled in the limit κ → ∞.…”
Section: Jhep10(2014)132 6 Conclusionsupporting
confidence: 57%
“…Furthermore, the same conclusion was reached more recently in [31] but with a different combination of T -dualities. What distinguishes the results of [32] and [31] is the way the various fields are scaled in the limit κ → ∞.…”
Section: Jhep10(2014)132 6 Conclusionsupporting
confidence: 57%
See 1 more Smart Citation
“…Various ways of taking this limit in the η deformed model have been studied [12,20,34,[52][53][54], with the limit of [52,53] having the particular algebraic interpretation as a contraction of the q deformed algebra [54].…”
Section: Discussionmentioning
confidence: 99%
“…The deformed background breaks the symmetry of AdS 5 ×S 5 to [U(1)] 6 , which urges to the new insight of its dual field theory which has to be explored yet. In order to understand the various aspects of the background one can look in to [25][26][27][28][29][30][31][32][33][34]. The perturbative world sheet scattering matrix of bosonic particles of the model was computed in [25].…”
Section: Jhep03(2015)010mentioning
confidence: 99%